2019
DOI: 10.1186/s12885-019-5959-8
|View full text |Cite
|
Sign up to set email alerts
|

High baseline Tie1 level predicts poor survival in metastatic breast cancer

Abstract: Background Angiopoietin growth factors (Angs) regulate angiogenesis and lymphangiogenesis by binding to the endothelial Tie2 receptor. Ang2 expression is elevated in tissue hypoxia and inflammation, which also induce cleavage of the extracellular domain of the orphan Tie1 receptor. Here we have examined if the concentrations of Ang2 and the soluble extracellular domain of Tie1 in patient plasma are associated with the prognosis of patients with metastatic breast cancer. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…This study was the first to demonstrate the function of Tie1 in gliomas. Tie1 is often studied in the occurrence of vascular development and cardiovascular diseases [10][11][12][13][14][15][16][17], At present, there are no reports on its relationship with glioma, particularly glioma stem cell viability. However, we employed bioinformatics software for predicting protein-protein interactions and found that Tie1 can interact with some cellular factors, particularly nerve growth factors such as BDNF, GDNF, and GFAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was the first to demonstrate the function of Tie1 in gliomas. Tie1 is often studied in the occurrence of vascular development and cardiovascular diseases [10][11][12][13][14][15][16][17], At present, there are no reports on its relationship with glioma, particularly glioma stem cell viability. However, we employed bioinformatics software for predicting protein-protein interactions and found that Tie1 can interact with some cellular factors, particularly nerve growth factors such as BDNF, GDNF, and GFAP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Tie1 is associated with angiogenesis, vascular maturation, tissue remodelling, and inflammation. Recent studies have also shown that elevated Tie1 expression is intimately associated with atherosclerosis and the stemness of cancer stem cells [12,[14][15][16][17]. However, there have beenno reports so far on the relationship between Tie1 and HuGSCs.…”
Section: Ivyspringmentioning
confidence: 99%
“…These proteins are crucial for the remodeling and maturation of tumor vasculature [67]. TIE1 is believed to form a complex with angiopoietins and sustain TIE2 signaling in contacting cells [68,69] and was found increased in several malignancies [70][71][72]. The exact functions of TIE1 in cancer remain unknown, but given the contributions of TIE1 and -2 to angiogenesis, their role in hypoxic tissue seems especially relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC, a female group of patients with adenocarcinoma and high expression of Tie1 had lower overall survival than those with a low expression of Tie1 [13]. In a recent phase II trial with taxane-bevacizumab combination chemotherapy, elevated levels of ANG2 and Tie1 in the blood plasma of patients with metastatic breast cancer were associated with shorter overall survival than baseline levels [14]. During hypoxia and in ammation, Tie1 was found to induce the antagonistic disruptive form of ANG2 [15,16].…”
Section: Introductionmentioning
confidence: 97%